Morphological characterization of Trichoderma spp. isolated from the oil palm rhizosphere in peat soils and its potential as a biological control for Ganoderma sp. in vitro - Rachmad Saputra; Fifi Puspita; Anthony Hamzah; Irfandri; Eka Suryani (Universitas Lancang Kuning, 2022)
Trichoderma sp. is a saprophytic fungus found in various environments, one of which is in the rhizosphere of oil palm plants which can be used to control Ganoderma and increase the resistance of oil palm plants from stem rot disease. This study aimed to characterize the morphology of Trichoderma spp. origin of peat land in oil palm plantations in Kampar Regency and screening the potential in controlling Ganoderma sp. Trichoderma spp. from oil palm rhizosphere was collected from the smallholder oil palm plantations in Deli Makmur Village, Kampar, Indonesia. This research was conducted by several observations, such as the hypovirulence test; identification of the morphology of Trichoderma spp. fungus; growth and diameter test of Trichoderma spp. fungus; test of the inhibitory ability of Trichoderma spp. fungus against Ganoderma sp. LPTUNRI-Gan002 isolate; test for hyperparasitism of the fungus Trichoderma spp., which has high antagonistic power against Ganoderma sp. isolate. Six Trichoderma spp. isolates had morphological characteristics similar to two species, i.e., Trichoderma harzianum (LPTUNRI-Trc001, Trc004, Trc005, and Trc006 isolates) and Trichoderma asperellum (LPTUNRI-Trc002 and Trc003). LPTUNRI-Trc003 had the highest diameter (90 mm), growth rate (32.66 mm/day), and the highest ability to suppress Ganoderma sp. LPTUNRI-Gan002 (91.03%) compared to the other five isolates.